Henry Heckelbeck and the race car derby - Coven, Wanda (Coven, Wanda. Henry Heckelbeck, 2021)
In this fifth Henry Heckelbeck adventure, Henry races to the finish in his first derby! Henry and his friends are going to race in a race car derby! The only problem is each racer has to build their own car. Can Henry magic together the perfect ride? Or will he crash and burn? With easy-to-read language and illustrations on almost every page, the Henry Heckelbeck chapter books are perfect for beginning readers.